The Impact of Occupational Therapy on Motor Function and Activities of Daily Living in Stroke Survivors - Majlessi Koupaei, Hamidreza; Farista, Rozina (Health Nexus, 2023)
The current study aims to examine the impact of occupational therapy on motor function and activities of daily living in stroke survivors. It presents a quasi-experimental study assessing the effect of occupational therapy on enhancing motor function and ADLs in stroke survivors. The study involved 30 participants divided into control and experimental groups. The measures include Fugl-Meyer Assessment (FMA) and Katz Index of Independence in Activities of Daily Living (ADL). Significant improvements were observed in the experimental group in both motor function and ADLs, as shown by ANOVA and post-hoc tests. The findings highlight the efficacy of occupational therapy in facilitating recovery and improving quality of life post-stroke, integrating traditional approaches with innovative technologies. The study also shows the necessity of occupational therapy in stroke rehabilitation and its holistic impact on physical recovery and patient well-being. For healthcare systems, these findings show the importance of allocating resources towards occupational therapy services for stroke survivors. This includes investing in advanced rehabilitation equipment and ensuring adequate staffing. Additionally, healthcare systems should consider developing collaborative models of care that involve multidisciplinary teams, including occupational therapists, to provide comprehensive and holistic treatment for stroke survivors.